Branding and Strategic Management to Build Student Loyalty in Islamic Education - Salsabilla, Imelia Sahda; Wahid, Abdul; Kurniawan, Cecep Soleh (Pascasarjana IAIN Kudus, 2025)
AbstractThis research identifies the strategic steps involved in planning, organizing, and implementing innovative teaching programs supported by institutional branding to attract and maintain student loyalty. A qualitative approach with case studies was employed to collect data through in-depth interviews, observations, and documentation. Strategic planning, including intensive training for ustadz/ustadzah and relevant teaching methods, creates a fun and effective learning experience for students. Organizing involves the recruitment of competent faculty, and optimal resource management supports institutional excellence. Implementing branding strategies through social media has also been proven to improve the institution’s image in the eyes of students and parents. Evaluating the implementation of this strategy shows its positive impact on student loyalty, which also contributes to strengthening the reputation and sustainability of Islamic educational institutions. This research shows that the success of Qur’anic guidance institutions depends on the integration of teaching innovations, branding strategies, and sustainable branding. This strategy attracts new students and ensures their long-term loyalty.Keywords: student loyalty, Islamic educational institutions, branding, organization, management strategy